PENERAPAN BALANCED SCORECARD SEBAGAI INDIKATOR DALAM PENGUKURAN KINERJA KOPERASI (STUDI PADA KPRI KARYA DHARMA SELONG) - Abdul Haris (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This study aims to determine the performance of KPRI "Karya Dharma" Selong from a financial perspective, customer perspective, internal business processes, learning and growth perspective throughthe Balanced Scorecard analysis. The method used is descriptive method. A study on the phenomenon orpopulation obtained by researchers of the subject in the form of individual, organizational, industry orany other perspective. The data used in this study comes from the Annual Member Meeting Report ofKPRI "Dharma Karya" Selong fiscal year 2011 to fiscal year 2015. These results indicate that theperformance measurement results KPRI "Dharma Karya" Selong seen from the perspective of financialand customer perspective is generally considered "fair". Meanwhile, if viewed from the perspective ofinternal business processes and learning and growth perspective is generally rated "Good". Theimplication of this finding is that KPRI "Dharma Karya" Selong can apply the method BalancedScorecard as a performance measurement system that can measure the performance of the cooperative ofcooperatives in a comprehensive or exhaustive.Keywords: Performance Measurement, Financial Perspective, Customer Perspective, internal business processes, learning and growth perspective, Balanced Scorecard